Embroidering Elegance: A Woman's Journey into the Treasures of Local Wisdom in Traditional Indonesian Weaving and Writing - Suryanti, Suryanti; Fakhrizal, Herwan; Akmal, Ahmad; Sundari, Sri; Eriswan, Eriswan (Journal of Pragmatics and Discourse Research, 2023)
This research explores women's empowerment through the traditional artistry of Songket Pandai Sikek in Tanah Datar, West Sumatera, Indonesia, focusing on the intricate fusion of skillful craftsmanship and written communication. The decline of traditional weaving practices, attributed to the advent of non-mechanical looms, prompts an investigation into the essence of Local Wisdom in women's empowerment through Songket Pandai Sikek. Utilizing a qualitative descriptive approach, the study employs written observations, interviews, and document analysis as data collection methods involving various informants. The findings, meticulously communicated through writing, highlight the profound significance of local wisdom interwoven into the art, sourced from written prose and oral traditions expressed in songs. Nature-inspired motifs in the Songket weaving process serve as intentional carriers of tales, expressed in prose or melody, becoming integral components of the fabric's narrative. The research also emphasizes the artisans' adaptability to changes, narrated through written narratives, illustrating the evolution and preservation of Pandai Sikek weaving. The study contributes valuable insights through the written word by examining the interplay of local wisdom, women's empowerment, and Songket Pandai Sikek's intricate artistry. It underscores the enduring allure of Songket Pandai Sikek and its pivotal role in empowering women /by incorporating local wisdom. Ultimately, the research articulates the cultural and social impact of this traditional craft in West Sumatera, establishing a meaningful connection between local wisdom, women's empowerment, and the meticulous artistry of Songket Pandai Sikek, all embedded with profound written and oral narratives.